Palma and the literary evenings at the house of Juana Manuela Gorriti: a literary space and socialization in Lima (1876-1877) - Pérez Garay, Carlos Alberto (2020)
The present work focuses on the friendship that originated in the 1850s between the author of Peruvian Traditions and the Argentinean writer, and in the meetings held at the Argentinian writer’s house in the city of Lima between the years 1876 and 1877. We will try to get to know the literary and socialization space developed in that gathering.